THE SPACE OF CONTINUOUS FUNCTIONS WITH $2$-NORMS - Shelvi Ekariani; MOCHAMMAD IDRIS; DODY ICHWANA PUTRA (Jurnal Matematika UNAND, 2026)
The purpose of this paper is to study the space of continuous functions, $C[a,b]$ as a $2$-normed space. In particular, we show that the space is complete with respect to some linearly independent set.